A Methodology and Tool for Mapping the Risk of Cumulative Effects on Benthic Habitats - Quemmerais-Amice, Frédéric; Barrere, Julien; La Rivière, Marie; Contin, Gabriel; Bailly, Denis (Frontiers in Marine Science, 2020)
The implementation of the European integrated marine policy poses many scientific challenges. Among them, the knowledge and understanding of interactions between anthropogenic pressures and ecological components is an important issue, particularly to help define Good Environmental Status, environmental targets and monitoring programs of the Marine Strategy Framework Directive (2008, MSFD). Cumulative effects assessment is a particularly complex issue requiring modeling tools and methods, as well as accurate data sets on human activities, anthropogenic pressures and ecological components. The results of these assessments are also uncertain and highly dependent on the calculation methods and assumptions, as well as on the data sets used. Within this context, we developed a technical and methodological approach to map the risk of cumulative effects on benthic habitats. These developments were initiated as part of the implementation of the MSFD to contribute to the diagnosis of the marine environment. Here we provide a demonstrator to illustrate the feasibility for mapping the risk of cumulative effects on benthic habitats, as well as the confidence index and the variability associated with this analysis. The method is based on a spatial analysis using a mapping of benthic habitats and their sensitivity to pressures, as well as the distribution and intensity of human activities and associated pressures. We collected and prepared relatively accurate and consistent data sets to describe human activities and benthic habitats. Data sets are embedded into a grid that facilitates the management and analysis of the data and exploitation of the results. The demonstrator consists of a relational database using the Spatial Query Language (SQL) language as well as data analysis scripts using the R language. The first demonstrator operations validated the main methodological and technical choices and helped to identify future developments needed to facilitate the appropriation and integration of these approaches in the implementation of public policies for the management of the marine environment.